2020
DOI: 10.1103/physrevb.101.085108
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal topological phononics in optomechanical arrays

Abstract: We propose a platform for robust and tunable non-reciprocal phonon transport based on arrays of optomechanical microtoroids. In our approach, time-reversal symmetry is broken by the interplay of photonic spin-orbit coupling, engineered using a state-of-the-art geometrical approach, and the optomechanical interaction. We demonstrate the topologically protected nature of this system by investigating its robustness to imperfections. This type of system could find application in phonon-based information storage an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…At the same time, microfabrication techniques have enabled small-scale optomechanical circuits capable of on-chip manipulation of mechanical and optical signals [3][4][5][6][7][8][9][10][11][12]. Building on these developments, theoretical proposals have shown that larger scale optomechanical arrays can be used to modify the propagation of phonons, realizing a form of topologically protected phonon transport [12][13][14][15][16]. Here, we report the observation of topological phonon transport within a multiscale optomechanical crystal structure consisting of an array of over 800 cavity-optomechanical elements.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…At the same time, microfabrication techniques have enabled small-scale optomechanical circuits capable of on-chip manipulation of mechanical and optical signals [3][4][5][6][7][8][9][10][11][12]. Building on these developments, theoretical proposals have shown that larger scale optomechanical arrays can be used to modify the propagation of phonons, realizing a form of topologically protected phonon transport [12][13][14][15][16]. Here, we report the observation of topological phonon transport within a multiscale optomechanical crystal structure consisting of an array of over 800 cavity-optomechanical elements.…”
mentioning
confidence: 90%
“…In conclusion, we have demonstrated a multiscale optomechanical crystal and observed topological transport of thermal phonons in the 0.3 GHz band over a bandwidth of 15 MHz. This novel design opens the door to implementing on-chip phononic circuits [13,15,16,39] with robust topological waveguides that have access to the full toolbox of optomechanics. Beyond cooling, mechanical lasing, sensitive read-out, and optical generation of nonclassical quantum states, this would also include the active optical control of topological circuits via local manipulation of mechanical modes (e.g., switching links between edge states).…”
mentioning
confidence: 99%
“…Since its observation by Huygens in the 17 th century, the synchronization of widely distinct systems have been shown to share remarkably universal features [1,2], fostering its exploration across many disciplines [3][4][5]. With the recent convergence among optical, mechanical and electrical waves using scalable microfabrication technologies, synchronization has emerged as a powerful tool targeted not only at technological applications, such as phaselock loops (PLLs) in radio-based communications [6][7][8], but also at developing the fundamentals of chaotic systems [9], injection locking [10][11][12], electro and optomechanical devices [13][14][15][16][17][18][19][20], nonlinear dynamics [21][22][23][24][25], network coupling [26][27][28][29], and quantum synchronization [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the controlling and transmission between solid state and flying state are subsequently realized in such system. For example, nonreciprocal phonon transport based on arrays of optomechanical microtoroids [19], nonreciprocal conversion between microwave and optical photons in electro-optomechanical systems [20] and unidirectional amplification in optical gain optomechanical systems [5]. Up to now, most of the studies are limited in the localized quantum effect to achieve nonreciprocal properties.…”
Section: Introductionmentioning
confidence: 99%